Phylogenetic and morphological revision sexual stages of the genus Paraphoma (Phaeosphaeriaceae) and next related species from clade of Ophiobolus-like (Phaeosphaeriaceae) - Mlčoch, Patrik; Matušinsky, Pavel (Phytotaxa, 2024)
This study brings new knowledge about the taxonomy of some fungal species that originally belong to the polyphyletic genus Leptosphaeria. Molecular-phylogeny and morphology methods were carried out for taxonomic revision of some taxa in the genus Leptosphaeria (L. clavispora, L. barriae, L. rubicunda and its similar species) and defined new taxonomic combinations of these species, namely Ophiobolus clavisporus (J. H.Mill. & Burton) Mlčoch, Chaetosphaeronema barriae (Shoemaker) Mlčoch and Paraphoma rubicunda (Rehm ex G. Winter) Mlčoch. In the genus Chaetosphaeronema, Ch. misuriniensis sp. nov. was described, and in the genus Paraphoma, Paraphoma betonicicola sp. nov. and P. moravica sp. nov. were described. Furthermore, the synoptic keys of species from Paraphoma rubicunda (Rehm ex Winter) Mlčoch comb. nov. morphological species group, and dichotomous keys for phragmosporous species of the order Pleosporales, which are known from dead stems of Lamiaceae and phragmosporous taxa associated with Lupinus (Fabaceae), are provided.